Identification of Hydroxyproline-Containing Proteins and Hydroxylation of Proline Residues in Rice - Liang, Ronghong; You, Li; Dong, Fang; Zhao, Xiaolu; Zhao, Jie (Frontiers in Plant Science, 2020)
The hydroxyproline-containing proteins (HCPs) among secretory and vacuolar proteins play important roles in growth and development of higher plants. Many hydroxyproline-rich glycoproteins (HRGPs), including Arabinogalactan proteins (AGPs), extensins (EXTs), and proline-rich proteins (PRPs), are identified as HCPs by bioinformatics approaches. The experimental evidence for validation of novel proline hydroxylation sites is vital for understanding their functional roles. In this study, the 62 HCPs containing 114 hydroxyproline (O, Hyp) residues were identified and it was found that hydroxylation of proline residues in the HCPs could either constitute attachment sites for glycans or have other biological function in rice. The glycomodules of AO, OA, OG, VO, LO, and OE were abundant in the 62 HCPs. Further analysis showed that the 22 of 62 HCPs contained both signal peptides and transmembrane domains, and the 19 HCPs only contained transmembrane domains, while 21 HCPs contained neither . This study indicated the feasibility of mass spectrometry-based proteomics combined with bioinformatics approaches for the large-scale characterization of Hyp sites from complex protein digest mixtures. Furthermore, the expression of AGPs in rice was detected by using β-GlcY reagent and JIM13 antibody. The results displayed that the AGPs were widely distributed in different tissues and organs of rice, especially expressed highly in lateral root, pollen and embryo. In conclusion, our study revealed that the HCPs and Hyp residues in rice were ubiquitous and that these Hyps could be candidates for linking to glycans, which laid the foundation for further studying the functions of HCPs and hydroxylation of proline residues in rice.